ANALISIS CAMPUR KODE BAHASA PERSIDANGAN DI PENGADILAN NEGERI PAYAKUMBUH - Wahyuni, Neneng; Ningsih, Asih Ria (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
Research problemis in using the language we have to see the context or situation. If the formal situation we use the Indonesian language and if the situation is not formal we may use local language or the other. Mixed code is the use of two or more languages ​​in a conversation. The trial is one of the official situations, so the language used is Indonesian. But sometimes in the trial process, this code mix is ​​very common. Based on observations and observations of researchers when the trial took place in court found mixed code. Based on this background, the author is interested and interested to examine the mixed language code trial in Payakumbuh district court. The purpose of this study is to describe the use of mixed language code trial in Payakumbuh District Court.